Institutions, regulation and performance the case of the Philippine telecommunications - Espos, Edna A. (2003)
A stable institution, efficient regulation and outstanding performance of the Philippine Telecommunications can pave the way for the realization of one of the four pillars of the 2001 national agenda, namely, low cost high speed connectivity that can boost the Information Communication Technology infrastructure. Furthermore, the interface of telecommunications vis-a-vis a nation's ability to maximize the prospects for development offered by ICT is beyond question. This study examines in detail the formulation and enforcement of the laws and regulations governing the telecommunication industry since it was liberalized. Lastly, it gives us insights on the latest developments in regulatory policy: what the government is doing to prepare the country for convergence and what measures it takes in order to address issues of weakness on the part of the National Telecommunications Commission as regulator over the various telecommunications firms new operating in the country, i.e., regulatory capture.
Keywords: Express Telecommunications Company, Incorporated (EXTELCOM); Franchise/Franchising; Information and communication technologies; Liberalization (Finance); National Telecommunications Commission (NTC); Philippine Long Distance Telephone Company; Telecommunications industry